2020
DOI: 10.1109/access.2020.3037685
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nonsinusoidal AC Loss of Superconducting Tapes Using Artificial Intelligence-Based Models

Abstract: Current is no longer sinusoidal in modern electric networks because of widespread use of power electronic-based equipments and nonlinear loads. Usually AC loss is calculated for pure sinusoidal current, while it is no longer accurate when current is nonsinusoidal. On the other hand, efficiency of cooling system in large scale power devices is dependent on accurate estimation and prediction of the heat load caused by AC loss in design stage. Therefore, estimation of nonsinusoidal AC loss of high temperature sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…SVMs techniques are used in the problem of classification, regression, and prediction models [21]. For the classification problems, hyperplanes are required in a multidimensional space separating data points of both fault classes.…”
Section: Svm Classifier Coupled With Bamentioning
confidence: 99%
“…SVMs techniques are used in the problem of classification, regression, and prediction models [21]. For the classification problems, hyperplanes are required in a multidimensional space separating data points of both fault classes.…”
Section: Svm Classifier Coupled With Bamentioning
confidence: 99%
“…AC loss could drastically increase when this happens [21,32] and as a consequence, the heat load of the machine increases. Therefore, it must be taken into account when estimating AC loss [39] and designing the most suitable cooling system, otherwise, it would either lead to thermal breakdown of the cooling system or temperature rise of the machine winding. Having high precision in AC loss calculation/estimation method together with meaningful experimental results would be a great help for manufacturing suitable HTS coils for the rotating electric machine to avoid such thermal runaway.…”
Section: Ac Loss Characteristicsmentioning
confidence: 99%
“…There is a gap in addressing the dependence of magnetization loss in HTS CC on the phase angle of harmonics of external magnetic field in literature [10]- [21]. Our previous study observed a drastic transport AC loss variation when the current harmonic is at different phase angle [22]- [23].…”
Section: Introductionmentioning
confidence: 97%